2007
DOI: 10.1530/rep-06-0051
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the requirement for Foxo3 in primordial follicle activation

Abstract: Primordial follicles are long-lived structures assembled early in life. The mechanisms that control the balance between the conservation and the activation of primordial follicles are critically important for fertility and dictate the onset of menopause. The forkhead transcription factor Foxo3 serves an essential role in these processes by suppressing the growth of primordial follicles, thereby preserving them until later in life. While other factors regulating primordial follicle growth have been described, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 57 publications
0
78
1
3
Order By: Relevance
“…Further, inhibition of AKT in neonatal rat ovary organ culture resulted in decreased CDK1/p27 expression and decreased phosphorylated FOXO3a and was associated with reduced oocyte apoptosis (Liu et al 2009). It is not, however, likely that FOXO3a is involved in cyst breakdown as FOXO3a knockouts demonstrate normal primordial follicle formation (John et al 2007). However, CDK1/p27 knockout mice show accelerated primordial follicle formation and CDK1/p27 is expressed in somatic cells surrounding cysts (Rajareddy et al 2007).…”
Section: Growth Factors and Signaling Moleculesmentioning
confidence: 99%
“…Further, inhibition of AKT in neonatal rat ovary organ culture resulted in decreased CDK1/p27 expression and decreased phosphorylated FOXO3a and was associated with reduced oocyte apoptosis (Liu et al 2009). It is not, however, likely that FOXO3a is involved in cyst breakdown as FOXO3a knockouts demonstrate normal primordial follicle formation (John et al 2007). However, CDK1/p27 knockout mice show accelerated primordial follicle formation and CDK1/p27 is expressed in somatic cells surrounding cysts (Rajareddy et al 2007).…”
Section: Growth Factors and Signaling Moleculesmentioning
confidence: 99%
“…PF assembly is normal in female mice bearing a null Foxo3 mutation ( John et al 2007). Immediately thereafter, however, PFs undergo global activation and grow in an essentially synchronized manner, resulting in ovarian hyperplasia by PND14.…”
mentioning
confidence: 99%
“…John et al (12) reported that as the downstream of PI3K/Akt, hyperphosphorylation of FoxO3a induced over-activation of primordial follicules (8,26,28). As previous studies have systematically reported that maintaining optimal activities of PI3K/Akt signaling pathway is essential for normal ovarian function, which not only regulates the balance between survival and activation of primordial follicles, but also is vital for the proliferation and differentiation of GCs (26)(27)(28).…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations have indicated that FoxO3a is highly expressed and localized to the nucleus during the dormancy of primordial follicles, then is phosphorylated and exported to the cytoplasm during follicular activation in mice (10). However, the activity of FoxO3a is suppressed in later-growing follicles, indicating that the downregulation of FoxO3a in oocytes may be a prerequisite for the initiation of oocyte growth during follicular activation (11,12).…”
Section: Introductionmentioning
confidence: 99%